Full blood count parameters in COVID-19 patients with disease severity, patient outcome and vaccination status - Omar, Mohd. Shah Fazly; Mohd Tajuddin, Syirah Nazirah; Md Noor, Sabariah; Seman, Zainina (Universiti Putra Malaysia, 2023)
Introduction: A link between full blood count (FBC) parameters with the severity and prognosis of individuals with coronavirus disease 2019 (COVID-19) infection is shown. We aim to identify changes in FBC parameters depending on patients’ characteristics, the severity of the disease and vaccination status. Methods: A cross-sectional retrospective laboratory study is done on 208 respondents who were selected from February 2021 to December 2022 in the Pathology Department of the Tuanku Ja’afar Hospital in Negeri Sembilan. All patients are confirmed COVID-19 positive by real-time reverse transcriptase-polymerase chain reaction (RT-PCR) of pharyngeal and nasal swab specimens. Patients are further classified based on their COVID clinical stages, severity, vaccination status and outcome. The statistical data are analysed using IBM SPSS version 27. Results: Severe patients have significantly lower absolute lymphocyte count (ALC), absolute monocyte count (AMC), absolute eosinophil count (AEC) and absolute basophil count (ABC) but higher mean platelet volume (MPV), absolute neutrophil count (ANC), neutrophil to lymphocyte ratio (NLR) and immature granulocytes (IG) compared to non-severe patients (p < 0.05). Similar findings are seen among non-survivors (p < 0.05). Fully vaccinated patients have significantly lower NLR and MPV but higher ALC, AMC, AEC and ABC than unvaccinated or partially vaccinated patients (p < 0.05). Conclusion: Selected FBC parameters of COVID-19 patients (platelets, ANC, NLR, MPV, ALC, AMC, AEC, and ABC) are significantly different depending on patients’ severity, outcome and vaccination status. These results might give a clear insight for clinicians to anticipate the severity and outcome of patients based on the patient’s FBC parameters.